2017
DOI: 10.18632/oncotarget.14900
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of anion exchanger 1 in esophageal squamous cell carcinoma

Abstract: Recent studies have described important roles for the anion exchanger (AE) in epithelial carcinogenesis and tumor behavior. The objectives of the present study were to investigate the role of AE1 in the regulation of genes involved in tumor progression and the clinicopathological significance of its expression in esophageal squamous cell carcinoma (ESCC). An immunohistochemical analysis was performed on 61 primary tumor samples obtained from ESCC patients who underwent esophagectomy. AE1 was primarily located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
(52 reference statements)
0
24
0
Order By: Relevance
“…Bodily and cellular functions are controlled by various factors including ions such as Na + , K + , Ca 2+ , Mg 2+ , Zn 2+ , and Cl − [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. On the one hand, pH (−log[H + ]) is recognized as one of classical items considered to be already fully understood in roles and mechanisms of homeostasis.…”
Section: Variety Of the Interstitial Fluid Phmentioning
confidence: 99%
“…Bodily and cellular functions are controlled by various factors including ions such as Na + , K + , Ca 2+ , Mg 2+ , Zn 2+ , and Cl − [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. On the one hand, pH (−log[H + ]) is recognized as one of classical items considered to be already fully understood in roles and mechanisms of homeostasis.…”
Section: Variety Of the Interstitial Fluid Phmentioning
confidence: 99%
“…We previously reported that several ion transporters are expressed in human ESCC and play crucial roles in multiple cell functions. For example, Na + /K + /2Cl - cotransporter 1 (NKCC1) regulates cell cycle progression [ 25 ], K-Cl cotransporter 3 (KCC3) regulates cell migration and invasion [ 26 ], anion exchanger 1 (AE1) functions as a regulator of proliferation, survival, migration, and invasion [ 27 ], Na + /H + exchanger 1 (NHE1) plays a suppressive role in proliferation, survival, migration, and invasion [ 28 ], and aquaporin 5 (AQP5) affects proliferation and cell survival [ 29 ]. The objectives of the present study were to investigate the role of CLIC1 in the proliferation, apoptosis, migration, and invasion of ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, cancer cells may require hypoxia-inducible AE2 distribution. Several reports including our previous study demonstrated that the expression of hypoxia-inducible factors was elevated with the change of pH regulators, such as carbonic anhydrase (CA), suggesting that they become effective prognostic factors in microenvironment where the expression of hypoxia-inducible factors is increased [ 11 , 13 , 30 ]. Although this mechanism needs to be elucidated in more detail in further studies, our results suggest the important and specific roles of AE2 at the IF of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The development and maintenance of such a microenvironment are directly driven by pH regulators, such as the anion exchanger (AE), Na + /H + exchanger (NHE), monocarboxylate transporter (MCT), vacuolar H+-ATPase, and carbonic anhydrase (CA) [ 5 7 ]. We previously investigated the functions of ion transporters [ 8 , 9 ], water channels [ 10 ], and pHi regulators including AE1 [ 11 ], NHE1 [ 12 ], and CA12 [ 13 ] in esophageal squamous cell carcinoma (ESCC). Our findings suggested that these cellular physiological factors are effective biomarkers, and their regulation may produce novel strategies for future therapies for ESCC [ 4 ].…”
Section: Introductionmentioning
confidence: 99%